The Role of Work Commitment in Organizations - Rizky, Teuku Emir; Rahayu, Sri; Mesra B (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the effect of human resource quality and work motivation on job satisfaction with work commitment as an intervening variable at BPJS Employment Aceh. This research employed a quantitative approach with an associative research design. The population consisted of all employees of BPJS Ketenagakerjaan Aceh, while the sample comprised 99 respondents selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 3.3.3 software. The results indicate that human resource quality has a positive and significant effect on both job satisfaction and work commitment. Work motivation also has a positive and significant effect on job satisfaction and work commitment. Furthermore, work commitment has a positive and significant effect on job satisfaction. The indirect effect analysis reveals that work commitment does not mediate the relationship between human resource quality and job satisfaction, but it successfully mediates the relationship between work motivation and job satisfaction. These findings suggest that improving work motivation and human resource quality plays a crucial role in enhancing employees' work commitment and job satisfaction at BPJS Ketenagakerjaan Aceh.